Exploring Consumer-Based Brand Equity In Bangladesh: A Study On Bangladesh Apparel Industry (Journal of Pharmaceutical Negative Results, 2023)
Organizations are constantly looking for effective strategies to develop a strong brand in today's cutthroat business climate. The study in this regard intends to analyze the effects of country of origin on brand equity dimensions based on Aaker’s consumer-based brand equity (CBBE) model with regards to the Bangladesh apparel industry. This paper further analyzed the role of brand equity dimensions namely brand awareness, brand image, perceived quality and brand loyalty on fashion apparel brand equity in Bangladesh. Data were collected through an online survey from 300 respondents residing Dhaka Metropolitan Area. Afterward, the collected data were examined using SPSS and SEM. The findings of the study revealed that the country of origin has a significant positive effect on brand loyalty and overall brand equity while having no significant positive effect on brand awareness, brand image, and perceived quality. Additionally, the result disclosed that the effect of brand awareness, brand image, perceived quality and brand loyalty on fashion apparel brand equity is insignificant. Hence, the study shed light on the possible rationale behind these divergent outcomes and emphasizes scrutinizing other dimensions which will strengthen the overall brand equity of this particular sector.